Українські біженці-антибільшовики у фортеці Фегераш, Румунія (1920–1923) - Bajenaru, C. (Київський національний університет імені Тараса Шевченка, 2021)
Фортеця Фегераш впродовж століть свого існування займала особливе місце в історії Румунії. Загальновідомими є факти, що вона використовувалась як потужна захисна фортеця, резиденція трансільванських князів, військовий гарнізон, комуністи ж перетворили її на в'язницю. Тим не менш, маловідомим є інший аспект її застосування – після 1918 року фортеця була притулком та прихистком для іноземних військових та цивільних біженців з України, які втікали від більшовицького "парового катка". У статті на основі архівних джерел та повідомлень місцевої преси розглядається цей короткий період кількасотрічного існування фортеці Фегераш.

Fagaras Fortress had over the centuries of its existence, a special importance in Romanian history, knowing both moments of glory and decay. It is known the fact that it has been successively a strong defensive fortress, residence for Transylvania's Princes, military garrison and communist prison. Nevertheless, it is less known or is not at all known another aspect, the one that the fortress had in some moments after 1918 the function of shelter and refuge for foreign military and civilians, how it was the case of hundreds of Ukrainians afflicting wanderers, fled from the front of Bolshevik steamroller. Regarding the last of these aspects we will talk in the next pages, trying to shape this moment from the century-old existence of the fortress as coherent and consistent as possible, even if the archivist sources or the information from the local press of that period are minimal.
Anti-Bolshevik Ukrainian Refugees in Fagaras Fortress – Romania (1920–1923)
Keywords: Фортеця Фегераш; притулок; табір; українці; Гнат Погоровський; Fagaras Fortress; refuge; encampment; Ukrainians; Hnat Porohivski